Curriculum Management and Power Relations: Strategies for Multicultural Character Development of Santri in Traditional Pesantren - Najib, Muhammad; Maskuri, Maskuri; Sa'id, M. Mas'ud (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze how curriculum is managed and enacted in a traditional pesantren and how these practices function as mechanisms for regulating knowledge, power relations, and the formation of santri character. The study employs a qualitative, ethnographic research design, with data collected through long-term participant observation, in-depth interviews with kiai, ustadz, santri, and pesantren administrators, and the analysis of relevant supporting documents. The findings reveal that the curriculum at PPMH Sidayu is not structured through formal written plans or organizational frameworks. Instead, it operates through informal, everyday learning practices such as pengajian kitab, the bandongan and sorogan methods, oral evaluations, and institutionalized forms of social habituation. The selection and distribution of learning materials, evaluation mechanisms, and managerial coordination occur informally and are accepted as part of the taken-for-granted institutional order. These practices not only transmit religious knowledge but also shape learning dispositions, acceptance of authority, and the social character of santri through affective experiences and social relations. The novel contribution of this study lies in its exploration of the pesantren curriculum as a social practice that operates through symbolic power relations and habituation rather than formal pedagogical structures. This research provides a deeper understanding of curriculum management in traditional Islamic educational institutions, suggesting that it should be seen as a flexible, socially embedded process, influenced more by symbolic authority and informal coordination than formal administrative systems. These findings have significant implications for curriculum studies and Islamic educational management within traditional religious institutions.